PENGARUH U-TURN TERHADAP KARAKTERISTIK ARUS LALU LINTAS DI RUAS JALAN CUT MUTIA BEKASI MENGGUNAKAN PKJI-2023 - Agus Riyadi; Muhammad Isradi (Universitas Lambung Mangkurat, 2025)
Cut Mutia Raya Road, located in East Bekasi, is a road that connects Bekasi City with Bekasi Regency and has a very important role in the development of Bekasi City and its surroundings. The high number of U-turn movements on this road section affects the performance of the road section, which causes disturbances for motorists both from the same direction and from the opposite direction and has the potential for traffic conflicts, in addition to congestion caused by the impact of the distance between the median opening facilities (U-turn). The aim of this study is to determine the characteristics of traffic flow on this road section using the PKJI-2023 method, get the performance value of the U-turn facility, and find out how much influence the U-turn facility has on the performance of the road section. The method used is by making direct observations in the field to obtain geometric data of road sections, traffic counting for the volume of vehicles on the road section, and those that turn back at the U-Turn facility to be further analyzed using the PKJI-2023 method and the 2005 U-Turn Planning Guidelines method. Based on the survey data in the field, the peak hour volume of vehicles on Wednesday, 13 November 2024, was 4.016 vehicles/hour (3.100 vcu/hour), with a Degree of Saturation (DJ) value of 0,74. The free flow speed is 55,2 km/h, and the MP passenger vehicle speed based on DJ is 46 km/h. The volume of vehicles making a U-turn at the U-turn is 731 vehicles/hour (406,6 vcu/hour). With a vehicle waiting time of 10,12s with a queue length of 3,12m and a delay of 12,04s.